How do physical fitness, nutritional status, and self-concept affect student learning outcomes in physical education with a focus on health and hygiene education? - Sepriani, Rika; Ockta, Yovhandra; Eldawaty, Eldawaty; Padli, Padli (Jurnal Konseling dan Pendidikan, 2024)
This study explores how physical fitness, nutritional status, and self-concept influence Physical Education (PE) learning outcomes at State Junior High School 13 Padang. Using a quantitative correlational approach, the research involved 58 students sampled from a population of 160. Data were gathered through physical fitness tests, Body Mass Index (BMI) measurements, self-concept questionnaires, and final PE grades. The results revealed that physical fitness contributes 5.18%, nutritional status contributes 6.78%, and self-concept contributes 9.33% to PE learning outcomes. Together, these factors explain 21.07% of the variance in students' PE performance. The analysis showed that each of these variables plays a significant role in shaping students' success in PE. To address the issues identified and enhance learning outcomes, the study recommends increasing the number of PE class hours, introducing school-based nutritional programs to improve students' diets, and developing initiatives to boost students' self-esteem and motivation. By focusing on these areas, schools can better support students' physical and psychological well-being, leading to improved educational outcomes in PE. This approach aims to provide a more holistic improvement in students' physical education, addressing both physical and mental aspects to foster better overall performance. Further research could examine the effectiveness of these interventions and their impact on broader educational goals.